Structural and kinetic characterization of mutant human uroporphyrinogen decarboxylases - Warby, C A; Phillips, J D; Bergonia, H A; Whitby, F G; Hill, C P; Kushner, J P (Cellular and Molecular Biology, 2009)
Porphyria cutanea tarda (PCT) is caused by inhibition of uroporphyrinogen decarboxylase (URO-D) activity in hepatocytes. Subnormal URO-D activity results in accumulation and urinary excretion of uroporphyrin and heptacarboxyl porphyrin. Heterozygosity for mutations in the URO-D gene is found in the familial form of PCT (F-PCT). Over 70 mutations of URO-D have been described but very few have been characterized structurally. Here we characterize 3 mutations in the URO-D gene found in patients with F-PCT, G318R, K297N, and D306Y. Expression of the D306Y mutation results in an insoluble recombinant protein. G318R and K297N have little effect on the structure or activity of recombinant URO-D, but the proteins display reduced stability in vitro.